HUBUNGAN KEHAMILAN RISIKO TINGGI DENGAN KEJADIAN NEONATUS RISIKO TINGGI DI RSUD TAMAN HUSADA BONTANG - Ririn Rochmawati,; Endah Wahyutri,; Nilam Noorma, (Jurnal Cakrawala Ilmiah, 2023)
Preface:Early identification of pregnancy risks is very important, because high risk pregnancies are often thought to be related with birth complications, thereby affecting the morbidity and mortality of babies born. The aim of this research is to determining the relationship between high risk pregnancies and high risk neonatesincidence. Methods:This cross sectional research was conducted in Taman Husada Bontang Regional Hospital from July-September 2023. 539 mothers who gave birth in here became the population and 85 of them were taken as samples using purposive sampling technique based on the Slovin formula. Pregnancy risk screening data was carried out using the Poedji Rochjati score, while high risk neonates were obtained from observation sheets. All data was analyzed using Spearman test. Result:From the screening results, it was found that 86% of respondents were in the high risk pregnancy category and 14% very high risk, and there’re 98% of babies who experience high risk neonates. Crosstabulation results showed that in high risk pregnancies there was a high risk neonates incidence of 98.6% babies, where as in very high risk pregnancies there was 91.7% babies who experienced high risk neonates. From Spearman test, the Sig. value (2 tailed) was obtained 0.000<0.05 with correlation coefficient 0.478. Conclusion: There’s a relationship between high risk pregnancy with incident of high risk neonates in Taman Husada Bontang Regional Hospital.